The spatial pattern of FDI: Some testable hypotheses - Pamela Bombarda (Graduate Institute of International Studies, 2007)
This paper is a simple extension of the standard FDI model of Markusen and Horstmann (1992). This latter predicts firms would supply nearby markets with exports but far away markets with FDI. Nevertheless, this does not match the spatial pattern in the data for many home nations and industries. We propose a model with heterogeneous firms where the spatial pattern of FDI depends upon distance-linked communications costs as well as trade costs; the resulting model lines up both with the aggregate knowledge-capital model evidence and the firm-level evidence of Helpman-Melitz-Yeaple, while still allowing individual firms to engage in FDI in nearby markets while supplying distant markets via exports.
Keywords: F12; F23; 330; intermediate goods; multinational firms; communication costs; Direktinvestition; Multinationales Unternehmen; Außenwirtschaftstheorie; Theorie